Business Integrity in Practice - Stachowicz-Stanusch, Agata (Business Expert Press, 2012)
Ebook from IG Library ; The quest for integrity in business is not only a reaction against malfeasance in business and associated calls for reform but also a search that stems from changes and new demands in the global business environment. Among the sources of these new demands are the expectations of stakeholders that corporations and their leaders will take more active roles as citizens within society and in the fight against some of the most pressing problems in the world, such as poverty, environmental degradation, defending human rights, corruption, and pandemic diseases. This book presents and critically discu.